2018
DOI: 10.1371/journal.pbio.2003611
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-mediated posttranslational modifications control neurotransmitter release by modulating complexin farnesylation and enhancing its clamping ability

Abstract: Nitric oxide (NO) regulates neuronal function and thus is critical for tuning neuronal communication. Mechanisms by which NO modulates protein function and interaction include posttranslational modifications (PTMs) such as S-nitrosylation. Importantly, cross signaling between S-nitrosylation and prenylation can have major regulatory potential. However, the exact protein targets and resulting changes in function remain elusive. Here, we interrogated the role of NO-dependent PTMs and farnesylation in synaptic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 79 publications
2
35
0
1
Order By: Relevance
“…25,27 The protein S-nitrosylation reaction (in which NO reacts with cysteine thiols to form S-nitrosylated proteins) is an important posttranslational modification and thus regulates protein structures and functions. 33,[39][40][41] which may cause significant oxidative damage on various target biomolecules, such as lipids, sugars, DNA, and proteins. 25,42 Functions of the NO System Inside Dental Pulp Tissue and the Involved Mechanisms…”
Section: Anmentioning
confidence: 99%
“…25,27 The protein S-nitrosylation reaction (in which NO reacts with cysteine thiols to form S-nitrosylated proteins) is an important posttranslational modification and thus regulates protein structures and functions. 33,[39][40][41] which may cause significant oxidative damage on various target biomolecules, such as lipids, sugars, DNA, and proteins. 25,42 Functions of the NO System Inside Dental Pulp Tissue and the Involved Mechanisms…”
Section: Anmentioning
confidence: 99%
“…In the brain, physiological NO signalling contributes to regulation of neuronal excitability [45,46], neurotransmitter release involved in learning and memory, synaptic plasticity and neuroprotection [47]. Impact of NO signalling on synaptic function is mediated via posttranslational modifications of proteins involved in vesicular release across different cellular systems and species [48][49][50][51] indicating the importance of this conserved signalling route. However, cytotoxic nitrergic signalling is associated with the immune response and plays a key role in regulating inflammatory processes and redox stress, ultimately contributing to neuronal degeneration.…”
Section: Neuroinflammatory No Signalling Is Augmentedmentioning
confidence: 99%
“…A recent wealth of evidence has demonstrated that free radicals, and most notably NO, play a crucial role in the regulation of stress effects and may be directly involved in the pathophysiology of stress-related disorders [13][14][15][16][17]. Under normal conditions, NO produced by the neuronal isoform of nitric oxide synthase (nNOS) is an important neurotransmitter associated with synaptic plasticity, memory formation, and neurotransmitter release [18,19]. Several studies have demonstrated that the binding partner of nNOS, nitric oxide synthase 1 adaptor protein (Nos1ap; also known as Cterminal PDZ ligand of neuronal nitric oxide synthase or CAPON), plays a novel role in mediating nNOS signaling and its interaction with the NMDA receptor [20,21].…”
Section: Introductionmentioning
confidence: 99%